Reactivation of Tuberculosis and COVID-19 in Pediatric Patients - Ünal, Gökçen; Pekcan, Sevgi; Metin Akcan, Özge; Keleş, Sevgi; Yılmaz, Aslı İmran; Eldeniz, Fadime Ceyda; Çağlar, Hanife Tuğçe; Özdemir, Mehmet; Poyraz, Necdet; Kılınç, Fahriye; Bulut, Ayşe (Journal of Pediatric Infectious Diseases, 2023)
Objective Mycobacterium tuberculosis is an immobile aerobic bacillus that causes tuberculosis (TB) disease. We aimed to evaluate the association between coronavirus disease 2019 (COVID-19), COVID-19-related drugs, TB reactivation, and TB incidence during the pandemic.Methods Eight patients who were diagnosed as having TB in Meram Medical Faculty, Necmettin Erbakan University between March 1, 2020, and December 31, 2021, at the beginning of the pandemic, were enrolled in this study. The presence of COVID-19 infection was confirmed using COVID-19 antibody tests and the patients' COVID-19 history. We evaluated the demographic data, laboratory findings, imaging tests, and pathology results of all patients.Results We checked all our patients with TB using COVID-19 antibodies (immunoglobulin [Ig]G + IgM) or polymerase chain reaction. Seven of the eight patients were female (87.5%). The median age was 16 years. Family screening of all patients was negative, and they had bacillus Calmette–Guérin vaccine scars. Two patients had chronic diseases. One was diagnosed as having primary ciliary dyskinesia in our department (patient no. 8) and the second was under follow-up by the rheumatology department with a diagnosis of juvenile idiopathic rheumatoid arthritis.Conclusion There has been an increase in the incidence of TB in children, especially in adolescents, during the pandemic period. This may be due to the pathogenic structure of the COVID-19 virus with an unknown mechanism. In addition, lifestyle changes and changes in health care policies during the pandemic may have caused this. Further research should be performed on this topic.
Keywords: COVID-19; tuberculosis; reactivation